Cyrus the Great, religion, and the conquest of ancient Anatolia - Medenieks, Selga Meta (Trinity College (Dublin, Ireland). Department of Classics, 2013)
With the invasion of Anatolia in the sixth century BC Cyrus the Great began a series of conquests that would form the Persian Empire. For his tolerance and, indeed, support of foreign religions during his rule, Cyrus has come to be regarded as the world's first humanitarian imperial leader. This reputation is based largely on actions in Babylonia and Palestine (related in the Cyrus Cylinder and the Old Testament), but little is known about Anatolia and the period in which his religious policies were probably formulated and first implemented.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin.